Long term outcomes among adults post transcatheter atrial septal defect closure: Systematic review and meta-analysis. (1st November 2018) - Alnasser, Sami; Lee, Douglas; Austin, Peter C.; Labos, Christopher; Osten, Mark; Lightfoot, David T.; Kutty, Shelby; Shah, Ashish; Meier, Lukas; Benson, Lee; Horlick, Eric
Abstract: Background: Transcatheter Closure (TC) has become the main stay therapy for many secundum atrial septal defects (ASD) based on short and intermediate term outcome data. Long-term safety and efficacy of this approach among adult patients however, is not well established. Methods and results: A comprehensive search of major electronic databases for studies reporting the long-term (≥5 year) outcomes post TC among adults yielded 114 studies, 9 of which had met the inclusion criteria. This included 1015 patients with a mean age of 45 years ± 5.5 years, two third were female with a mean follow up duration 6.4 years ± 2.7 years. The weighted proportions of long-term mortality and stroke with 95% confidence intervals (CI) were 2.4% (95%CI 0.9%–6.1%) and 2.1% (95%CI 0.7%–5.7%) respectively. Atrial arrhythmia occurred in 6.5% (95%CI 3.5%–11.7%) and atrial fibrillation in 4.9% (95%CI 1.9%–11.7%). ASD related re-interventions were encountered in 2.3% (95%CI 1.0%–5.4%) and residual shunt in 4.2% (95% CI 1.3%–12.4%), with 1 case of suspected device erosion 0.9% (95%CI 0.4–2.2%). Frame fractures and late migrations were observed at 4.2% (95%CI 1.5%–11.5%) and 1.2% (95%CI 0.3%–4%) respectively. No cases of occluder endocarditis or thrombosis were reported. In conclusion: This is the first study that systematically analyzes the long-term outcomes after TC providing important estimates for various clinical and occluder related outcomes. The analysis suggests preserved long-term safety post TC; however, this is limited due to the variable quality of available evidence and requires further assessment by larger studies with more comprehensive follow-up data. Highlights: This is the first systematic review of studies examining long-term outcomes post transcatheter ASD closure. Despite the guideline supported role of transcatheter ASD closure, data on long-term outcomes post TC is scant. The analysis provides estimates for various long-term outcomes post TC including clinical and device related ones. Studies were retrospective and of low methodoligical quality.